2022
DOI: 10.48550/arxiv.2206.11278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chandra, HST/STIS, NICER, Swift, and TESS Detail the Flare Evolution of the Repeating Nuclear Transient ASASSN-14ko

Abstract: ASASSN-14ko is a nuclear transient at the center of the AGN ESO 253−G003 that undergoes periodic flares. Optical flares were first observed in 2014 by the All-Sky Automated Survey for Supernovae (ASAS-SN) and their peak times are well-modeled with a period of 115.2 +1.3 −1.2 days and period derivative of −0.0026 ± 0.0006. Here we present ASAS-SN, Chandra, HST /STIS, NICER, Swift, and TESS data for the flares that occurred in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In addition to studying supernovae (SNe; e.g., Bose et al 2018Bose et al , 2019Hoeflich et al 2021;Chen et al 2022), ASAS-SN obtains data for a broad range of transients, multi-messenger searches, and variable sources. For transients, these include tidal disruption events (TDEs; e.g., Holoien et al 2019b,c, 2020, Hinkle et al 2021, Payne et al 2022, novae (e.g., Kawash et al 2021bKawash et al , 2022, dwarf novae (e.g., Kawash et al 2021a), and changing look or other active galactic nuclei (AGN; e.g., Neustadt et al 2020, Hinkle et al 2022, Holoien et al 2022. There are multi-messenger searches associated with both neutrino (e.g., IceCube Collaboration et al 2018, Necker et al 2022) and gravitational wave (e.g., de Jaeger et al 2022) events.…”
mentioning
confidence: 99%
“…In addition to studying supernovae (SNe; e.g., Bose et al 2018Bose et al , 2019Hoeflich et al 2021;Chen et al 2022), ASAS-SN obtains data for a broad range of transients, multi-messenger searches, and variable sources. For transients, these include tidal disruption events (TDEs; e.g., Holoien et al 2019b,c, 2020, Hinkle et al 2021, Payne et al 2022, novae (e.g., Kawash et al 2021bKawash et al , 2022, dwarf novae (e.g., Kawash et al 2021a), and changing look or other active galactic nuclei (AGN; e.g., Neustadt et al 2020, Hinkle et al 2022, Holoien et al 2022. There are multi-messenger searches associated with both neutrino (e.g., IceCube Collaboration et al 2018, Necker et al 2022) and gravitational wave (e.g., de Jaeger et al 2022) events.…”
mentioning
confidence: 99%
“…However, when the delay due to circularization is comparable to the fallback timescale, the resulting TDE light curve will be drastically flattened (Mockler et al 2019), resulting in a much shallower rise in luminosity than the one observed in ASASSN-14ko. In addition, the bright, fast evolving X-ray emission in ASASSN-14ko (Payne et al 2022a(Payne et al , 2022b) also indicates efficient disk formation. Hence, for ASASSN-14ko, the circularization delay and the viscous timescale are both expected to be negligible.…”
Section: Constraints On the Mean Stellar Densitymentioning
confidence: 99%
“…where κ T is the Thomson opacity for electron scattering, M env ≈ ΔM is the mass of the outflow, and r in and r out are the inner and outer radius of the wind. Payne et al (2022a) estimated the blackbody radius of the photosphere during a single flare using UV data, which expands from 10 14.2 -10 14.9 cm as the luminosity rises to its maximum. This means r in of the reprocessing layer where the wind originates is 10 14.2 cm and r out ≈ 10 14.9 cm when the UV luminosity reaches its peak value.…”
Section: Constraints On the Stellar Massmentioning
confidence: 99%
“…Additionally, several other nuclear transients have had rise slopes measured with TESS, with flatter rises than these TDEs. These include the repeating TDE ASASSN-14ko, with a rise slope of α = 1.01 ± 0.07 (51) for the first flare observed by TESS when assuming a single power-law model, and α = 1.10 ± 0.04 and α = 1.50 ± 0.10 for the first and the second flares observed by TESS, respectively, when assuming a curved power-law model (88), and the ANT ASASSN-20hx, with a rise slope of α = 1.05 ± 0.06 (89).…”
Section: Tessmentioning
confidence: 99%